Urban freight in Dublin : an integrated policy framework for sustainable distribution - Finnegan, Clare (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2010)
Urban goods movement is essential to life in a city. Every product and service we avail of must be transported from where it is sourced to where it is sold. At a wider level, urban freight transport is the engine driving economic activity. Retail trade and industry are dependent on a timely and reliable goods distribution system. However, although urban goods transport is vital in supporting economic development, it also has unsustainable impacts for the environment, for the economy and also for society. There are two key features of urban freight research, which influence this thesis. Firstly, the limited amount of urban freight data available has made it difficult for European cities to devise policies that are grounded in what is actually happening in reality. Secondly, analysis of urban freight has tended to occur in isolation of other transport policies.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin